Synthesis of a resin monomer-soluble polyrotaxane crosslinker containing cleavable end groups - Seo, Ji-Hun; Nakagawa, Shino; Hirata, Koichiro; Yui, Nobuhiko (Beilstein Journal of Organic Chemistry, 2014)
A resin monomer-soluble polyrotaxane (PRX) crosslinker with cleavable end groups was synthesized to develop degradable photosetting composite resins. The PRX containing 50 α-cyclodextrins (α-CDs) with disulfide end groups was initially modified with n-butylamine to obtain a resin monomer-soluble PRX. The PRX containing 13 n-butyl groups per α-CD molecule was completely soluble in conventional resin monomers such as 2-hydroxyethyl methacrylate (HEMA) and urethane dimethacrylate (UDMA). The synthesized n-butyl-containing PRX was further modified with 2-aminoethyl methacrylate to provide crosslinkable acrylic groups onto PRX. The prepared resin monomer-soluble PRX crosslinker was successfully polymerized with a mixture of HEMA and UDMA to provide photosetting plastic. It was confirmed that the Vickers hardness of the prepared plastic was greatly decreased after treatment with dithiothreitol. This indicates that the resin monomer-soluble PRX crosslinker can be applied to design degradable photosetting plastics potentially used in the industrial or biomedical field.
Keywords: α-cyclodextrin; composite resin; disulfide; polyrotaxane; Vickers hardness